Elemen Estetis Koreografi Tari Sambut Ringkeh Gemulai Di Kota Prabumulih - Indah Jamihaq Chaniago; Yessi Anggraini R Erinna Rahmalia; Rully Rochayati (Yayasan Baru Haji Samsudin, 2024)
This study discusses the aesthetic elements of the choreography of the Ringkeh Gemulai welcome dance which is a development of the Seinggok Sepemunyian welcome dance in the city of Prabumulih. Ringkeh Gemulai dance is a dance for welcoming guests of honor which is an important part of welcoming guests. The purpose of this study will be to discuss how the aesthetic elements of the choreography of the Ringkeh Gemulai welcome dance are created to become distinctive in it. This research method uses qualitative, which is a research process that begins with the rules of thinking and compiling the basic assumptions outlined in the research. From the results of the research it was found that the creation of a new dance as the Ringkeh Gemulai welcoming dance was a development of the Seinggok Sepemunyian welcoming dance.